Reference values of vertical jumping performances and anthropometric characteristics in trained adolescents - Aouichaoui, C.; Tounsi, M.; Mrizak, I.; Tabka, Z.; Trabelsi, Y. (Science & Sports, 2018)
Objective: The aim of this study was to provide percentile values for vertical jumping performances and anthropometric characteristics for athletic Tunisian children and adolescent.